2014
DOI: 10.2166/washdev.2014.026
|View full text |Cite
|
Sign up to set email alerts
|

Fecal sludge management: a comparative analysis of 12 cities

Abstract: This paper outlines the findings of a fecal sludge management (FSM) initial scoping study in twelve cities. This short, desk-based study used innovative tools to assess the institutional context and the outcome in terms of the amount of fecal sludge safely managed. A range of cities was included in the review, all in low-and middle-income countries.None of the cities studied managed fecal sludge effectively, although performance varied. Where cities are seeking to address fecal sludge challenges the solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 1 publication
1
97
1
3
Order By: Relevance
“…Though there is systematic evidence showing that sewerage interventions, another form of contained FSM, are associated with decreased incidence of diarrhea and enteric infection, onsite containment with emptying and transport has not been studied 19. Further, in contrast to our findings, recent city-level assessments of FSM have shown that long-term management of onsite fecal sludge is generally poor and may lead to nonfunctional toilets and backflow of excreta into homes during floods, contaminating the household environment 7,17. Given that we did not have the ability to assess the frequency or quality of FSM longitudinally, we cannot definitively make conclusions about the long-term effectiveness of the onsite containment in place.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Though there is systematic evidence showing that sewerage interventions, another form of contained FSM, are associated with decreased incidence of diarrhea and enteric infection, onsite containment with emptying and transport has not been studied 19. Further, in contrast to our findings, recent city-level assessments of FSM have shown that long-term management of onsite fecal sludge is generally poor and may lead to nonfunctional toilets and backflow of excreta into homes during floods, contaminating the household environment 7,17. Given that we did not have the ability to assess the frequency or quality of FSM longitudinally, we cannot definitively make conclusions about the long-term effectiveness of the onsite containment in place.…”
Section: Discussioncontrasting
confidence: 84%
“…While management of fecal sludge in low-income, urban areas is generally poor, the associations between FSM and fecal contamination or enteric infection within that environment have not been examined 7. There is a need to understand how fecal contamination and enteric infection vary with toilets and FSM in the urban environment.…”
Section: Introductionmentioning
confidence: 99%
“…If users cease open defecation and consistently use clean toilets, we still might not achieve optimal health impacts as toilets may continue to drain or empty somewhere other than into a sealed pit or sanitary sewer . We observed a number of toilet drainage systems without flow that contaminated the community environment, but upgrading dysfunctional infrastructure was beyond the scope of our intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Data available on sewerage for most countries from a published paper (Baum, Luh, and Bartram 2013) and on fecal sludge management from on-site systems for 12 countries (Peal et al 2014).…”
Section: Sanitationmentioning
confidence: 99%